Lesson learnt from an EEG-based experiment with ADHD children in Malaysia - Hisyam, Syariffanor; Abdul Rahman, Abdul Wahab (Springer Verlag, 2016)
There are growing interests among researchers worldwide pertaining to efficacy of electroencephalography (EEG) as diagnostic tools and noninvasive treatment for children with special needs. However, there are very limited studies discuss the efficacy of EEG-based experiment protocols among young children with ADHD particularly from the perspective of human-computer interaction methodologies. Thus, this paper provides some background on related studies in EEG for children with attention-deficit/hyperactive disorder (ADHD) and some insights on Malaysia experience with regards to ADHD detection and intervention programs. The lesson learnt presented in this paper highlights the factors that affect young children participation in EEG-based experiments that is relevant and beneficial for researchers who are working with children with special needs. © Springer International Publishing Switzerland 2016.